A scalable and durable polydimethylsiloxane-coated nanoporous polyethylene textile for daytime radiative cooling - Wang Tong; Wu Xinyu; Zhu Qian; Chen Yinggang; Zhang Shuqi; Gu Min; Zhang Yinan (Nanophotonics, 2023)
Radiative cooling technology with zero-energy consumption and zero-carbon emission has drawn enormous attention. However, the high-cost manufacture, limited scalability, and narrow application scopes remain major impediments to radiative cooling commercialization. Here, we present a bilayer PDMS/nanoPE fabricated by an automatic film applicator for high-performance passive daytime radiative cooling. The nanoPE underlayer maximizes the reflection of sunlight and the transparent PDMS top-layer dramatically enhances the infrared emissivity of pristine nanoPE across the atmospheric transparency window (∆E 8–13 μm = 0.85). The obtained PDMS/nanoPE simultaneously allows a high solar reflectance of 0.94 and a thermal emittance of 0.94, enabling a sub-ambient cooling of 4.5 °C with a maximum of 7.6 °C in rooftop test and a theoretical net cooling power of 65 W/m2. A distinct temperature reduction of more than 10 °C can be achieved in comparison with pristine PDMS film. Integration of the hydrophobicity, durability, robust mechanical strength, and industrial scalability, we believe this work will provide practical and efficient solutions to cooling vehicles, buildings, and the human body in a simple and low-cost manner.